Impact of longevity on greenhouse gas emissions and profitability of individual dairy cows analysed with different system boundaries. (29th May 2018) - Grandl, F.; Furger, M.; Kreuzer, M.; Zehetmeier, M.
Abstract : Dairy production systems are often criticized as being major emitters of greenhouse gases (GHG). In this context, the extension of the length of the productive life of dairy cows is gaining interest as a potential GHG mitigation option. In the present study, we investigated cow and system GHG emission intensity and profitability based on data from 30 dairy cows of different productive lifetime fed either no or limited amounts of concentrate. Detailed information concerning productivity, feeding and individual enteric methane emissions of the individuals was available from a controlled experiment and herd book databases. A simplified GHG balance was calculated for each animal based on the milk produced at the time of the experiment and for their entire lifetime milk production. For the lifetime production, we also included the emissions arising from potential beef produced by fattening the offspring of the dairy cows. This accounted for the effect that changes in the length of productive life will affect the replacement rate and thus the number of calves that can be used for beef production. Profitability was assessed by calculating revenues and full economic costs for the cows in the data set. Both emission intensity and profitability were most favourable in cows with long productive life, whereas cows that had not finished their first lactation performed particularly unfavourably with regard to their emissions per unit of product and rearing costs were mostly not repaid. Including the potential beef production, GHG emissions in relation to total production of animal protein also decreased with age, but the overall variability was greater, as the individual cow history (lifetime milk yield, twin births, stillbirths, etc.) added further sources of variation. The present results show that increasing the length of productive life of dairy cows is a viable way to reduce the climate impact and to improve profitability of dairy production.